Kreativitas Guru dalam Meningkatkan Hasil Belajar Siswa pada Pembelajaran Tematik Kelas 1 di Madrasah Ibtidaiyah Negeri Kauman Utara Jombang - Sitoresmi Arineng Tiyas (JURNAL LENTERA : Kajian Keagamaan, Keilmuan dan Teknologi, 2018)
Creativity is the ability to generate ideas and new solutions which are useful to solve the problems and challenges faced in everyday life. Thematic learning is learning that uses theme to linkseveral subjects that gives meaningful experience for students. Learning result is the change in behavior as a result of education process in accordance with the purpose of education. The purposes of this study are to: (1) knowthe form of teachers’ creativity that can improve students’ learning outcomes in thematic learning of class 1 MIN North Kauman, Jombang, (2) know any factors that are capable of shaping the creativity of teachers in improving students’ learning outcomes of class 1 MIN North Kauman, Jombang in thematic learning. To achieve several purposes above, the researcher used descriptive quantitative research design and data collection techniques are observation, interviews, and documentations. The instrument used is rubric creativity of teachers and Rubric syntax performance of thematic learning. Data were analyzed by statistic analysis and descriptive analysis. The results showed that, (1) the forms of teachers’ creativity that can improve the students’ learning outcomes in thematic learning, involves:able to instill the values ​​of life for students, able to interact with the students, give the students the chance to ask questions and give feedbacks, provide an opportunity for students to discuss, properly allocate time, innovated in learning, able to make the students be enthusiastic to learn. (2) Several factors that can shape the creativity of teachers in improving the students’ learning outcomes in thematic learning, includes: a learning experience, educational background, openness towards experience, intrinsic motivation, the Professional Network.